Penerapan Angsuran Pajak Penghasilan Pasal 25 Bagi Wajib Pajak Badan untuk Efisiensi Keuangan CV Visi Printing - Penus Sinurat; Putri Kemala Dewi Lubis; Evi Suryani Harahap; Elsa Situmorang; Tamaria br. Sidebang (Economic Reviews Journal, 2024)
This study discusses the implementation of Article 25 Income Tax (PPh) installments for corporate taxpayers, specifically at CV Visi Printing, and its impact on the company's financial efficiency. Article 25 PPh is a tax paid periodically throughout the fiscal year based on estimated tax liabilities, aimed at helping companies manage their tax obligations more effectively. This research employs a qualitative method with an analysis of the financial statements of CV Visi Printing for the year 2022. The results indicate that the Article 25 PPh installment applied by CV Visi Printing, amounting to Rp 3,553,000 per month, positively affects the company's cash flow efficiency. This gradual tax payment helps the company maintain liquidity and reduces the burden of a large tax payment at the end of the year. Furthermore, with proper tax planning, CV Visi Printing can allocate financial resources more effectively to support other operational activities. The implementation of this tax installment also enhances the company's tax compliance, avoiding potential penalties, and maintaining the company's financial stability in the long term. The study concludes that the application of Article 25 PPh installments plays a crucial role in improving the company's financial efficiency through better cash flow management and optimal tax planning.